Rural entrepreneurship - Kusio, Tomasz (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: The issue of rural development is an important topic from the perspective of the science of territorial development for several reasons. First, from the perspective of the growing importance of cities, with which the depopulation of the countryside is associated. Secondly, from the point of view of the development opportunities of non-urbanized areas, whose position in the context of fund distribution is weak. Finally, from the point of view of the possibility of diversifying food production, to which much attention is currently being paid in Europe and around the world. However, as studies show, not only the existence, but the development of rural areas is a determinant of the development of urban areas. Aim: The purpose of the article is to demonstrate that rural development continues to be a significant challenge, while especially important for this development is the involvement of people — entrepreneurial leaders. Results: As a result of the study, it was possible to gain input in the form of knowledge regarding the differential impact of the rural development factors identified in the study. The phenomenon of the possibility of digitization of social and business life, which has emerged as globalization has progressed, and quite clearly as a result of the pandemic, has shown that it is a factor of great importance in leveling the marginalization of rural areas. What’s more, the entrepreneurship of rural leaders is a key element in building strategies for the development of these areas, even outweighing the factor of a financial and administrative nature.